BDT223 -Invertebrate and Vertebrate Zoology (Zoologi Invertebrata dan Vertebrata) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pusat Pengajian Sains Kajihayat, 2024)
Second Semester Examination 2023/2024 Academic Session February 2024 BDT223 -Invertebrate and Vertebrate Zoology (Zoologi Invertebrata dan Vertebrata) Duration : 2 hours (Masa: 2jam)